NOLM based DPSK Signal Regeneration - Striegler, Arne; Meißner, Markus; Cvecek, Kristian; Sponsel, Klaus; Leuchs, Gerd; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2005)
We present a nonlinear optical loop mirror (NOLM)-based 2R-regenerator setup, which is capable of regenerating signals modulated in phase-sensitive modulation formats. In a conventional NOLM, fluctuations of the signal amplitude are converted into phase fluctuations. Therefore, it is not suitable for regeneration of signals, modulated in formats such as differential phase-shift keying (DPSK) or duobinary. In this letter, we present a modified NOLM setup for 2R-regeneration taking return-to-zero DPSK as an example. © 2005 IEEE.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.nolmba
Keywords: All-optical regeneration; Differential phase-shift keying (DPSK); Nonlinear optical loop mirror (NOLM)